Student Mathematical Representation Ability with Reflective Cognitive Style in Solving Geometric Problems - Fitratur Rahmah; Gatot Muhsetyo; Santi Irawati (Jurnal Pendidikan Sains, 2019)
Abstract: This research aims to describe the mathematical representation ability of students with reflective cognitive style in solving geometric  problems. The subjects of this study were two students whose reflective cognitive style were selected based on the results of the MFFT test. The research method used was descriptive research with a qualitative approach. The ability of mathematical representation was described based on three standards of mathematical representation ability, namely; (1) creating and using representations to organize, record, and communicate mathematical ideas, (2) choosing, using and translating between representations to solve problems, (3) using representations to create models and interpret mathematical, physical, and social phenomena. The results showed that subjects with reflective cognitive style can use mathematical representation capabilities well from various types of representations, namely visual images, verbal written texts, and mathematical expressions.Key Words: mathematical representation ability, reflective cognitive style, geometric problemAbstrak: Riset ini bertujuan untuk mendeskripsikan kemampuan representasi matematis siswa bergaya kognitif reflektif dalam menyelesaikan masalah bangun datar. Subjek penelitian ini adalah dua siswa yang bergaya kognitif reflektif yang dipilih berdasar hasil tes MFFT. Metode penelitian yang digunakan adalah penelitian deskriptif dengan pendekatan kualitatif. Kemampuan representasi matematis dideskripsikan berdasar tiga standar kemampuan representasi matematis, yaitu; (1) membuat dan menggunakan representasi untuk mengorganisasikan, mencatat, dan mengkomunikasikan ide-ide matematika, (2) memilih, menggunakan dan menerjemahkan antar representasi untuk menyelesaikan masalah, (3) menggunakan representasi untuk membuat model dan menginterpretasi fenomena matematis, fisik, dan sosial. Hasil penelitian menunjukkan bahwa subjek dengan gaya kognitif reflektif dapat menggunakan kemampuan representasi matematis dengan baik dari berbagai jenis representasi, yaitu visual gambar, verbal teks tertulis, dan ekspresi matematis.Kata kunci: kemampuan representasi matematis, gaya kognitif reflektif, masalah geometris